Synchronicity - Jung C.G. (London, 1972)
Jung was intrigued from early in his career with coincidences, especially those surprising juxtapositions that scientific rationality could not adequately explain. He discussed these ideas with Albert Einstein before World War I, but first used the term "synchronicity" in a 1930 lecture, in reference to the unusual psychological insights generated from consulting the I Ching. A long correspondence and friendship with the Nobel Prize-winning physicist Wolfgang Pauli stimulated a final, mature statement of Jung's thinking on synchronicity, originally published in 1952 and reproduced here. Together with a wealth of historical and contemporary material, this essay describes an astrological experiment Jung conducted to test his theory. Synchronicity reveals the full extent of Jung's research into a wide range of psychic phenomena.
Keywords: Coincidence